OPTIMALISASI PERAN TPQ DALAM MENINGKATKAN KEMAMPUAN BACA AL-QUR’AN ANAK DI TPQ NURUDDIN DESA BANJAR KECAMATAN WIDANG KABUPATEN TUBAN - M. Khoirul Muzakki; Himmatul Aliyah (LPPM Institut Agama Islam Uluwiyah Mojokerto, 2024)
This study aims to describe the efforts of TPQ Nuruddin in Banjar Village to improve children's Qur’an reading skills and to identify the challenges faced in the process. Using a qualitative descriptive approach through observation, interviews, and documentation, the findings show that the TPQ applies a tiered learning system, various teaching methods, and regular teacher training to enhance students’ reading quality. These efforts positively affect children’s accuracy in tajwid and fluency in reading the Qur’an. The main obstacles include low learning motivation, limited parental support, and inadequate learning facilities. TPQ Nuruddin plays an essential role in nurturing a Qur’anic generation with strong moral character and love for the Qur’an.